Determinants of Village Proliferation: Evidence from West Kalimantan Province - Santi Rahmawati; Eny Sulistyaningrum (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2022)
This research was conducted to determine the dominant factors which influenced the proliferation of village. As commonly known, these factors are used to accelerate development based on community aspirations. West Kalimantan Province was selected as the object of research since this province is the third largest province in Indonesia but only has few numbers of municipalities. In order to speed up the development in West Kalimantan, the local government needs to proliferate the region into small ones. It will make the regional government easier to manage its control than that of municipality with a larger area. This research used logit estimation in analysis and employed data from the Statistics Indonesia of West Kalimantan Province. The findings show that there were a number of factors affecting the proliferation of villages in West Kalimantan Province in 2008–2018, namely population, unemployment, poverty and regional head periods. Conversely, variables that did not significantly influence were HDI, GRDP and regional income variables. Meanwhile, other factors that also had a significant effect, but reduce the chances of proliferation of village were average rubber production and the percentage of state electricity consumption